O problema da referência a objetos não-existentes na Teoria da suposição de João Buridan - Roberta Magalhaes Miquelanti (2009)
This work intends to investigate the way of the medieval author John Buridan answers the problem of the reference of non-denotative terms, that is, terms which refer to non-existent objects, within the medieval terminist theory, specially the Supposition Theory. It focuses on one special case of non-existent objects: chimaera. The buridaniantheory answers the question of the meaning and reference of non-denotative terms making use of the semantic complexity of language and avoiding the postulation of a special type of existence of these objects.